Solid-state battery
By adopting solid-state battery design in lithium metal batteries, a vertical graphite layer composed of graphite sheets modified by magnetic substances is solved, and the safety hazards and electrical performance problems caused by lithium dendrites and dead lithium are achieved, achieving high energy density and fast charging effects.
Patent Information
- Application Number
- CN202411991409.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-28
AI Technical Summary
Lithium metal batteries have safety hazards and poor performance due to the existence of lithium dendrites and dead lithium, and the production environment and energy consumption requirements are also demanding.
The solid-state battery design is adopted, wherein the negative electrode includes a negative current collector, a graphite layer and a coating layer. The graphite layer is composed of a graphite sheet modified by magnetic substance. The graphite sheet is perpendicular to the negative electrode current collector and is separated, and the negative electrode surface capacity is smaller than the positive electrode surface capacity.
High energy density and fast charging are achieved, which slows down the impact of lithium dendrites and dead lithium, and reduces environmental control and energy consumption burden.
Smart Images

Figure CN119725767A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium batteries, and in particular to a solid-state battery. Background Art
[0002] Electric vehicles and intelligent multifunctional electronic products urgently need electrochemical energy storage devices with high energy density, long cycle life, fast charging support and high safety. In recent years, lithium metal with ultra-high theoretical energy density has attracted widespread attention. However, due to its high chemical reactivity, lithium metal anode is prone to side reactions with liquid electrolytes. At the same time, lithium deposition during charging is prone to form lithium dendrites, causing safety hazards. During discharge, lithium dissolution will produce dead lithium, causing polarization growth and rapid degradation of cycle performance.
[0003] Some researchers have introduced solid electrolytes into lithium metal batteries, intending to use the non-flammable and mechanically strong properties of solid electrolytes to improve the safety of lithium metal batteries and obtain a battery system with high energy density and high safety. However, lithium dendrites can still grow along the grain boundaries of solid electrolytes, and there is a risk of piercing the solid electrolyte and short-circuiting. Moreover, even if the solid electrolyte is non-flammable, the dead lithium powder produced during the charging and discharging process still has a very high reactivity. The above two points still leave some hidden dangers to the safety of solid-state lithium metal batteries, and the electrical performance of lithium metal batteries under solid electrolytes is also an issue that needs attention.
[0004] In addition, lithium metal, as a light metal with very active chemical properties, reacts easily with moisture in the air and is also easily slowly oxidized by oxygen in the air. This undoubtedly puts very stringent requirements on the production environment and production safety control of lithium metal batteries, and also brings a very large energy consumption burden to production. Summary of the invention
[0005] In order to solve the above-mentioned technical problems, the purpose of the present invention is to provide a solid-state battery; the solid-state battery provided in the present application has a high energy density, and on the basis of ensuring the energy density, it also supports fast charging, reduces the impact of lithium dendrites and dead lithium, and has a relatively low environmental control and energy consumption burden.
[0006] The technical solution provided by the present invention is as follows: A solid-state battery, comprising a positive electrode, a negative electrode and a solid electrolyte, wherein the negative electrode comprises: Anode current collector; A graphite layer coated on at least one side of the negative electrode current collector; A coating layer applied on the graphite layer; The graphite layer comprises graphite sheets modified by magnetic substances, wherein at least part of the graphite sheets are perpendicular to the negative electrode current collector and the graphite sheets are separated from each other; Moreover, the surface capacity of the negative electrode is smaller than the surface capacity of the positive electrode.
[0007] Preferably, the magnetic material-modified graphite sheet is at least one of a magnetic material-modified nitrogen-sulfur-doped graphite sheet, a phosphorus-doped graphite sheet, and a selenium-doped graphite sheet; and / or, The graphite layer also includes a first binder and a first ion conductor, and the mass ratio of the graphite sheet modified with a magnetic substance, the first binder, and the first ion conductor is (70-95):(1-15):(1-15).
[0008] Preferably, the first binder is at least one of styrene-butadiene rubber, lithium carboxymethyl cellulose, polyacrylic acid, and polyacrylonitrile; The first ion conductor is at least one of lithium lanthanum titanium oxide, lithium lanthanum zirconium oxide or their doping materials.
[0009] Preferably, the coating layer comprises at least one of Li3BO3-Li2CO3, Li3PO4, Li4SiO4, Li2ZrO3; and / or, The coating layer has a thickness of 20 nm to 2 μm.
[0010] Preferably, the negative electrode is prepared by a wet process, and an external magnetic field is applied after the graphite layer slurry is coated, so that at least part of the graphite sheets in the graphite layer are perpendicular to the negative electrode current collector.
[0011] Preferably, the positive electrode comprises a positive electrode current collector and a positive electrode composite layer; The positive electrode composite layer includes a positive electrode active material, and the positive electrode active material particles have a coating layer outside; The positive electrode active material includes at least one of lithium cobalt oxide, lithium nickel cobalt manganese oxide, and lithium-rich manganese-based; The coating layer includes at least one of lithium aluminum titanium phosphate, lithium lanthanum titanium oxide, lithium lanthanum zirconium oxide or their doping materials.
[0012] Preferably, the coating amount of the coating layer is 0.5wt% to 5wt% of the positive electrode active material; and / or, The positive electrode composite layer also includes a conductive agent, a second binder, and a second ion conductive agent; and the mass ratio of the positive electrode active material with a coating layer, the conductive agent, the second binder, and the second ion conductive agent is (70~95):(1~10):(1~5):(1~15).
[0013] Preferably, the conductive agent includes at least one of conductive graphite, carbon nanotubes, and graphene; The second binder includes at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, vinylidene fluoride-trifluoroethylene, and polytetrafluoroethylene; The second ion-conducting agent includes at least one of a sulfide solid electrolyte and a halide solid electrolyte; wherein the sulfide solid electrolyte is Li 11−x M 2−x P 1+x S 12 (M = Ge, Sn, Si), Li6PS5X (X = Cl, Br, I) at least one; the halide solid electrolyte is Li3MCl6 (M = Y, Er, In, Sc), Li 3−x M 1−x Zr x At least one of Cl6 (M = Y, In, Er, Yb), Li3MBr6 (M = Y, Er, Ho).
[0014] Preferably, the positive electrode is prepared by a dry method, wherein the positive electrode active material with a coating layer, a conductive agent, a second binder and a second ion conductive agent are mixed and fiberized at 10-25° C., and then pressed into a film at 100-180° C.
[0015] Preferably, the electrolyte includes polytetrafluoroethylene, and any one of a sulfide solid electrolyte, an oxide solid electrolyte, and a halide solid electrolyte; In terms of weight percentage, polytetrafluoroethylene accounts for 1% to 15% of the electrolyte; Sulfide solid electrolyte for Li 11−x M 2−x P 1+x S 12 At least one of (M = Ge, Sn, Si), Li6PS5X (X = Cl, Br, I); The oxide solid electrolyte is at least one of lithium aluminum titanium phosphate, lithium lanthanum titanium oxide, lithium lanthanum zirconium oxide or their doping materials; The halide solid electrolyte is Li3MCl6 (M=Y, Er, In, Sc); The electrolyte is made of polytetrafluoroethylene and at least one of a sulfide solid electrolyte, an oxide solid electrolyte and a halide solid electrolyte, which are mixed and fiberized at 15-30° C. and then pressed into a film at 100-180° C.
[0016] The present application provides a solid-state battery, comprising a positive electrode, a negative electrode and a solid electrolyte, wherein the negative electrode comprises: a negative electrode current collector; a graphite layer coated on at least one side of the negative electrode current collector; a coating layer coated on the graphite layer; the graphite layer comprises graphite sheets modified with a magnetic substance, wherein at least part of the graphite sheets are perpendicular to the negative electrode current collector and the graphite sheets are separated from each other; and the negative electrode surface capacity is smaller than the positive electrode surface capacity. The solid-state battery provided by the present application has a graphite layer on at least one side of the negative electrode current collector, and at least part of the graphite sheets in the graphite layer are perpendicular to the negative electrode current collector. Due to the different arrangement directions of the graphite sheets, the graphite sheets are naturally separated from each other and have gaps. When lithium ions migrate from the positive electrode to the negative electrode, they can be first embedded in the graphite layer and then deposited on the interlayer and surface between the vertical graphite sheets to form a graphite composite lithium metal structure to ensure that the effect of lithium embedding and deposition is good; and, the present application limits the negative electrode surface capacity to be less than the positive electrode surface capacity, that is, the solid-state battery N / P is much less than 1, and the vertical setting of the graphite sheet and the negative electrode current collector is coordinated. Since the vertical structure has a good lithium deposition foundation, the generation of lithium dendrites is suppressed, and the lithium is smoothly stripped during discharge, and the energy density of the overall battery core is improved. The solid-state battery provided by the present application replaces the lithium metal negative electrode with the above-mentioned negative electrode, which reduces the problem of lithium metal reaction or oxidation in the production process, reduces the difficulty of production, and reduces the high requirements for the production environment.
[0017] The solid-state battery provided in this application has a high energy density, and on the basis of ensuring the energy density, it also supports fast charging, reduces the impact of lithium dendrites and dead lithium, and has a relatively low environmental control and energy consumption burden.
[0018] In the present application, the graphite layer can be coated on one side or both sides of the negative electrode current collector. The graphite layer is coated with a coating layer at the same time, that is, the coating layer is located on the side of the graphite layer away from the negative electrode current collector.
[0019] The preferred magnetic material modified graphite sheet is specifically a magnetic material modified nitrogen-sulfur doped graphite sheet, which has better lithium affinity, is more conducive to inhibiting the generation of lithium dendrites, and promotes the smooth stripping of lithium during discharge. In addition, phosphorus or selenium doped graphite sheets can also be used.
[0020] Preferably, the graphite layer also includes a first binder and a first ion conductor. More preferably, the first binder is at least one of styrene-butadiene rubber, lithium carboxymethyl cellulose, polyacrylic acid, and polyacrylonitrile; the first ion conductor is at least one of lithium lanthanum titanium oxide, lithium lanthanum zirconium oxide, or their doping materials. Then, the spaces between the graphite sheets are filled with the first binder and the first ion conductor, which is conducive to the deposition of lithium ions. Lithium aluminum titanium phosphate will react with the lithium-embedded negative electrode, so it is not used as the first ion conductor of the negative electrode graphite layer.
[0021] The doping material of lithium lanthanum titanium oxide specifically refers to lithium lanthanum titanium oxide doped with metal elements. For example, lithium lanthanum zirconium oxide is doped with tantalum to form a lithium lanthanum zirconium tantalum oxide solid electrolyte. Similarly, the doping material of lithium lanthanum zirconium oxide also refers to lithium lanthanum zirconium oxide doped with metal elements.
[0022] The coating layer preferably includes at least one of Li3BO3-Li2CO3, Li3PO4, Li4SiO4, and Li2ZrO3. The thickness of the coating layer is preferably 20nm~2μm. Li3BO3-Li2CO3, Li3PO4, Li4SiO4, Li2ZrO3, etc. used in the coating layer are all single ion conductors, with high ion conductivity and lower interface impedance, which helps to improve the charge and discharge rate of the battery, and promote the uniform distribution and deposition of lithium ions on the surface of the negative electrode, and alleviate the volume change on the negative electrode side to a certain extent.
[0023] After the graphite layer is dried and rolled, the coating layer can be formed by methods known in the art, such as chemical vapor deposition, spray coating, screen printing, electrochemical deposition, physical vapor deposition, and the like.
[0024] In the present application, the negative electrode surface capacity is smaller than the positive electrode surface capacity by adjusting the coating weight of the graphite layer so that the negative electrode surface capacity is smaller than the positive electrode surface capacity. Preferably, the negative electrode is prepared by a wet process, that is, the reagent of the graphite layer (graphite sheets modified with magnetic substances, or graphite sheets modified with magnetic substances, a first binder and a first ion conductive agent) is mixed with deionized water to form a slurry, which is then coated on at least one side of the negative electrode current collector and dried to form a graphite layer. After coating, an external magnetic field is applied (which can be achieved using a magnetic field transmitting device) so that at least part of the graphite sheets modified with magnetic substances in the slurry are oriented perpendicular to the negative electrode current collector, and the graphite sheets of this part are separated from each other. In addition, the negative electrode surface capacity can be controlled by controlling the coating amount of the slurry in the process.
[0025] Preferably, the positive electrode includes a positive electrode current collector and a positive electrode composite layer; the positive electrode composite layer includes a positive electrode active material, and the positive electrode active material particles have a coating layer; the positive electrode active material includes at least one of lithium cobalt oxide, lithium nickel cobalt manganese oxide, and lithium-rich manganese base; the coating layer includes at least one of lithium aluminum titanium phosphate, lithium lanthanum titanium oxide, lithium lanthanum zirconium oxide or their doping materials. Each particle of the positive electrode active material is coated with a coating layer, which significantly improves safety and ion dynamics. Similarly, the doping materials of lithium aluminum titanium phosphate, lithium lanthanum titanium oxide, and lithium lanthanum zirconium oxide refer to doping materials generated by the metal elements (such as tantalum) of lithium aluminum titanium phosphate, lithium lanthanum titanium oxide, and lithium lanthanum zirconium oxide.
[0026] More preferably, the positive electrode composite layer further includes a conductive agent, a second binder, and a second ion conductive agent. The second ion conductive agent preferably includes at least one of a sulfide solid electrolyte and a halide solid electrolyte. The use of a solid electrolyte to mix the positive electrode and the structure of the positive electrode active material with a coating layer can further improve safety and ion dynamics.
[0027] It is more preferred that the positive electrode is prepared by a dry process. The positive electrode active material with a coating layer, the conductive agent, the second binder and the second ion conductive agent are mixed evenly in a mixer, and then the mixture is placed in a high-speed air flow mill for fiberization and mixing of polytetrafluoroethylene, and then the fiberized powder is transferred to a dry film making machine, and is finely pressed into a continuous film at high temperature and rolled into a coil after trimming to form a positive electrode. The temperature range for mixing and fiberizing the powder is 15~30℃, and the temperature range for pressing the fiberized powder into a film is 100℃~180℃.
[0028] The preferred electrolyte includes polytetrafluoroethylene, and any one of a sulfide solid electrolyte, an oxide solid electrolyte, and a halide solid electrolyte; in terms of weight percentage, polytetrafluoroethylene accounts for 1% to 15% of the electrolyte, and the rest is a solid electrolyte.
[0029] Since the negative electrode surface capacity is limited to that of the positive electrode in this application, it is bound to cause the precipitation of lithium metal in the negative electrode to form a graphite / lithium metal composite negative electrode, and Li 3−x M 1−x Zr x The two halide electrolytes Cl6 (M = Y, In, Er, Yb) and Li3MBr6 (M = Y, Er, Ho) are more unstable to lithium metal, so the halide solid electrolyte used as the electrolyte is Li3MCl6 (M = Y, Er, In, Sc). The halide electrolytes that can be used in the second ion conductor as part of the positive electrode composite layer include the above three.
[0030] The preferred electrolyte is composed of polytetrafluoroethylene and at least one of a sulfide solid electrolyte, an oxide solid electrolyte, and a halide solid electrolyte, which are mixed and fiberized at 15-30°C, a temperature range that can ensure the fiberization effect; and then pressed into a film at 100-180°C.
[0031] The solid-state battery provided in the present application is prepared by respectively manufacturing the positive electrode, the negative electrode and the electrolyte, and then obtaining the bare cell through the lamination and / or winding process known in the art, and then obtaining the solid-state battery through welding, packaging, isostatic pressing, formation and secondary packaging, and is equipped with the outer casing, the pole ears and other components known in the art. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0033] Figure 1 This is a scanning electron microscope image of the graphite layer in Example 1 of the present invention; Figure 2 This is a scanning electron microscope image of the graphite layer in Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0034] In order to enable those skilled in the art to better understand the technical solutions in this application, the technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0035] Example 1 A solid-state battery, consisting of a positive electrode, an electrolyte, and a negative electrode; Preparation of positive electrode: positive electrode active material (0.5 wt% lithium nickel cobalt manganese oxide coated with lithium titanium aluminum phosphate), conductive agent (carbon nanotubes), second binder (polytetrafluoroethylene), second ion conductive agent (Li6PS5Cl) are compounded according to the mass ratio of 80:3:2:15, mixed evenly in a mixer, and then placed in a high-speed air flow mill for fiberization and mixing of the binder, and the temperature is maintained at 22°C, and then the fiberized powder is transferred to a dry multi-roll hot pressing film machine, and finely pressed into a continuous film at 120°C, and at the same time pressed and compounded with the positive electrode current collector aluminum foil and rolled into a roll after trimming, thereby obtaining a positive electrode, which is die-cut for standby use; Preparation of negative electrode: The nitrogen-sulfur doped graphite sheets modified with magnetic material, the first binder (styrene-butadiene rubber and lithium carboxymethyl cellulose in a mass ratio of 2:1) and the first ion conductor (lithium lanthanum titanium oxide) are uniformly mixed with deionized water in a mass ratio of 85:3:12 to form a slurry, which is then covered on both sides of the negative electrode current collector. The coating weight is adjusted so that the negative electrode surface capacity is smaller than the positive electrode surface capacity, so that the N / P of the solid-state battery is 0.4, and then placed under a magnetic field launch device to dry to form a graphite layer, so that the graphite sheets in the graphite layer are perpendicular to the negative electrode current collector, and the graphite sheets in this part are separated from each other. After the graphite layer is dried and rolled, a 50nm thick Li3BO3-Li2CO3 coating layer is coated on its surface by chemical vapor deposition, thereby obtaining a negative electrode consisting of a surface coating layer and a lower graphite layer, which is die-cut for use. Among them, the photo of the graphite layer is shown in the figure. Figure 1 As shown, from Figure 1 It can be seen that the graphite sheet is perpendicular to the negative electrode current collector.
[0036] Preparation of electrolyte: The sulfide solid electrolyte Li6PS5Cl and polytetrafluoroethylene are mixed evenly in a mixer at a mass ratio of 98:2, and then the mixture is placed in a high-speed air flow mill for fiberization and mixing of the polytetrafluoroethylene. The temperature during mixing and fiberization is 19°C. The fiberized powder is then transferred to a dry film making machine, precision pressed into a continuous film at 150°C, and the edges are cut and rolled into a coil, thereby obtaining the electrolyte.
[0037] The positive electrode, negative electrode and electrolyte are stacked to obtain a bare cell, and then a solid-state battery is obtained through welding, packaging, isostatic pressing, formation and secondary packaging.
[0038] Example 2 Preparation of the positive electrode: The difference from Example 1 is that the positive electrode active material is 0.8 wt % lithium cobalt oxide coated with lithium aluminum titanium phosphate, and the second ion conductor is a halide solid electrolyte Li3InCl6, and the rest is the same as Example 1; Preparation of negative electrode: The difference from Example 1 is that the first ion conductor is lithium lanthanum zirconium oxide, and the coating layer is 100nm Li3PO4 prepared by chemical deposition method, and the rest is the same as Example 1; Preparation of electrolyte: The difference from Example 1 is that the solid electrolyte is lithium lanthanum zirconium oxide, and the mass ratio of lithium lanthanum zirconium oxide to polytetrafluoroethylene is 96:4, and the rest is the same as Example 1; The positive electrode, negative electrode and electrolyte are stacked to obtain a bare cell, and then a solid-state battery is obtained through welding, packaging, isostatic pressing, formation and secondary packaging.
[0039] Example 3 Preparation of the positive electrode: The difference from Example 1 is that the positive electrode active material is a lithium-rich manganese-based coated with 0.6 wt % lithium aluminum titanium phosphate, and the second ion conductor is a halide solid electrolyte Li3YCl6, and the rest is the same as Example 1; Preparation of negative electrode: The difference from Example 1 is that the coating layer is 50nm Li4SiO4 prepared by chemical deposition method, and the rest is the same as Example 1; Preparation of electrolyte: The difference from Example 1 is that the solid electrolyte is a halide solid electrolyte Li3YCl6, and the mass ratio of Li3YCl6 to polytetrafluoroethylene is 98:2, and the rest is the same as Example 1; The positive electrode, negative electrode and electrolyte are stacked to obtain a bare cell, and then a solid-state battery is obtained through welding, packaging, isostatic pressing, formation and secondary packaging.
[0040] Comparative Example 1 Preparation of the positive electrode: The positive electrode active material (0.5 wt% lithium nickel cobalt manganese oxide coated with lithium titanium aluminum phosphate), the conductive agent (carbon nanotubes), the second adhesive (polytetrafluoroethylene), and the second ion conductive agent (Li6PS5Cl) are mixed evenly in a mixer at a mass ratio of 80:3:2:15, and then the mixture is placed in a high-speed air flow pulverizer for fiberization and mixing of the adhesive, maintaining the temperature at 22°C, and then the fiberized powder is transferred to a dry multi-roller hot pressing film machine, and precision pressed into a continuous film at 120°C, and at the same time pressed and compounded with the positive electrode current collector aluminum foil and rolled into a roll after trimming, thereby obtaining the positive electrode, which is die-cut for use.
[0041] Preparation of negative electrode: The nitrogen-sulfur doped graphite sheet modified with magnetic material, the first binder (styrene-butadiene rubber and lithium carboxymethyl cellulose mass ratio of 2:1) and the first ion conductor (lithium lanthanum titanium oxide) are uniformly mixed with deionized water in a mass ratio of 85:3:12 to form a slurry, which is then covered on both sides of the negative electrode current collector. The coating weight is adjusted so that the negative electrode surface capacity is smaller than the positive electrode surface capacity, so that the solid-state battery N / P is 0.4, and then placed under a magnetic field launch device to dry to form a graphite layer, so that the graphite sheets in the graphite layer are perpendicular to the negative electrode current collector, and the graphite sheets in this part are separated from each other. After the graphite layer is dried and rolled, it is die-cut for use.
[0042] Preparation of electrolyte: The sulfide solid electrolyte Li6PS5Cl and polytetrafluoroethylene are mixed evenly in a mixer at a mass ratio of 98:2, and then the mixture is placed in a high-speed air flow mill for fiberization and mixing of the polytetrafluoroethylene. The temperature during mixing and fiberization is 19°C. The fiberized powder is then transferred to a dry film making machine, precision pressed into a continuous film at 150°C, and the edges are cut and rolled into a coil, thereby obtaining the electrolyte.
[0043] The positive electrode, negative electrode and electrolyte are stacked to obtain a bare cell, and then a solid-state battery is obtained through welding, packaging, isostatic pressing, formation and secondary packaging.
[0044] Comparative Example 2 Preparation of positive electrode: the same as that of comparative example 1.
[0045] Preparation of negative electrode: Only 50μm pure lithium is used as the negative electrode, and it is die-cut for later use.
[0046] Preparation of electrolyte: Same as Comparative Example 1.
[0047] The positive electrode, negative electrode and electrolyte are stacked to obtain a bare cell, and then a solid-state battery is obtained through welding, packaging, isostatic pressing, formation and secondary packaging.
[0048] Comparative Example 3 Preparation of positive electrode: the same as that of comparative example 1.
[0049] Preparation of negative electrode: Ordinary graphite sheet, the first binder (styrene-butadiene rubber and lithium carboxymethyl cellulose in a mass ratio of 2:1) and the first ion conductor (lithium lanthanum titanium oxide) are uniformly mixed with deionized water in a mass ratio of 85:3:12 to form a slurry, which is then covered on both sides of the negative electrode current collector. The coating weight is adjusted so that the negative electrode surface capacity is smaller than the positive electrode surface capacity, so that the N / P of the solid-state battery is 0.4. After the graphite layer is dried and rolled, a 50nm thick Li3BO3-Li2CO3 coating layer is coated on its surface by chemical vapor deposition, thereby obtaining a negative electrode consisting only of a graphite layer, which is then die-cut for use. The photo of the graphite layer is shown in the figure. Figure 2 As shown, from Figure 2 It can be seen that under normal circumstances, the graphite sheet and the negative electrode current collector are not in a vertical state, and the graphite sheets are not separated from each other.
[0050] Preparation of electrolyte: Same as Comparative Example 1.
[0051] The positive electrode, negative electrode and electrolyte are stacked to obtain a bare cell, and then a solid-state battery is obtained through welding, packaging, isostatic pressing, formation and secondary packaging.
[0052] Comparative Example 4 Preparation of the positive electrode: The positive electrode active material (lithium nickel cobalt manganese oxide), the conductive agent (carbon nanotubes), and the second adhesive (polytetrafluoroethylene) are mixed evenly in a mixer at a mass ratio of 95:3:2, and then the mixture is placed in a high-speed air flow pulverizer for fiberization and mixing of the adhesive, maintaining the temperature at 20°C, and then the fiberized powder is transferred to a dry multi-roller hot pressing film machine, and precision pressed into a continuous film at 120°C, and at the same time pressed and compounded with the positive electrode current collector aluminum foil, trimmed and rolled into a coil, thereby obtaining the positive electrode, which is die-cut for use.
[0053] Preparation of negative electrode: The nitrogen-sulfur doped graphite sheet modified with magnetic material, the first binder styrene-butadiene rubber and lithium carboxymethyl cellulose are uniformly mixed with deionized water in a mass ratio of 95:3:2 to form a slurry, which is then coated on both sides of the negative electrode current collector. The coating weight is adjusted so that the negative electrode surface capacity is smaller than the positive electrode surface capacity, so that the solid-state battery N / P is 0.4, and then placed under a magnetic field launch device to dry to form a graphite layer, so that the graphite sheets in the graphite layer are perpendicular to the negative electrode current collector, and the graphite sheets in this part are separated from each other. After the graphite layer is dried and rolled, it is die-cut for use.
[0054] Preparation of electrolyte: Same as Comparative Example 1.
[0055] The positive electrode, negative electrode and electrolyte are stacked to obtain a bare cell, and then a solid-state battery is obtained through welding, packaging, isostatic pressing, formation and secondary packaging.
[0056] The solid-state batteries prepared in the above-mentioned Examples 1 to 3 and Comparative Examples 1 to 4 were tested for cycle performance and safety performance, and the results obtained are as follows: Table 1 Solid-state battery cycle performance test results
[0057] Table 2 Solid-state battery cycle performance test results
[0058] By comprehensively comparing the preparation processes of the above embodiments and comparative examples and the corresponding cycle and safety test results, the analysis is as follows: Compared with the embodiments, Comparative Example 1 lacks a coating layer at the negative electrode, resulting in poor contact between the negative electrode and the electrolyte and a large interface impedance. Therefore, the polarization is large during the cycle and the cycle life is lower than that of the embodiments. In addition, due to the lack of a coating layer to help lithium ion deintercalation and deposition, dendrites are more easily formed, resulting in a decrease in safety performance.
[0059] Compared with the embodiments, in Comparative Example 2, only lithium metal is used as the negative electrode. A short circuit caused by dendrite penetration soon occurs during the cycle, and its safety performance is significantly reduced due to the direct deposition of lithium metal, which shows the superiority of the negative electrode in the embodiments.
[0060] Compared with the embodiments, in Comparative Example 3, the negative electrode lacks graphite sheets that are perpendicular to the negative electrode current collector, and the graphite sheets are separated from each other, which makes the lithium deintercalation basis poor, making it easier to form dendrites and dead lithium during the subsequent lithium deposition process, so the cycle performance and safety performance are reduced.
[0061] Compared with the embodiments, in Comparative Example 4, the positive and negative electrodes do not contain the corresponding ion conductive agent, so that the ion transmission inside the electrode is blocked and the polarization is very large, so normal charging and discharging cannot be performed.
[0062] In this scheme, the positive and negative electrodes are coated and blended with corresponding solid electrolytes, which significantly improves safety and ion dynamics. The nitrogen-sulfur doped graphite layer used in the negative electrode has an N / P ratio of less than 1 and the graphite sheet is perpendicular to the negative electrode current collector, which can improve the energy density of the overall battery cell, have a good lithium deposition foundation and better lithium affinity, inhibit the generation of lithium dendrites, and promote the smooth stripping of lithium during discharge. In addition, the single-ion conductor coating layer on the graphite layer has higher ion conductivity and lower interface impedance, which helps to improve the charge and discharge rate of the battery and promote the uniform distribution and deposition of lithium ions on the negative electrode surface, and alleviate the volume change on the negative electrode side to a certain extent. In summary, this scheme shows great superiority and advancement.
[0063] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A solid-state battery, comprising a positive electrode, a negative electrode and a solid electrolyte, characterized in that: The negative electrode comprises: Anode current collector; A graphite layer coated on at least one side of the negative electrode current collector; A coating layer applied on the graphite layer; The graphite layer comprises graphite sheets modified by magnetic substances, wherein at least part of the graphite sheets are perpendicular to the negative electrode current collector and the graphite sheets are separated from each other; Moreover, the surface capacity of the negative electrode is smaller than the surface capacity of the positive electrode.
2. The solid-state battery according to claim 1, characterized in that: The graphite sheet modified with magnetic material is specifically at least one of nitrogen-sulfur doped graphite sheet, phosphorus-doped graphite sheet and selenium-doped graphite sheet modified with magnetic material; and / or, The graphite layer also includes a first binder and a first ion conductor, and the mass ratio of the graphite sheet modified with a magnetic substance, the first binder, and the first ion conductor is (70-95):(1-15):(1-15).
3. The solid-state battery according to claim 2, characterized in that: The first binder is at least one of styrene-butadiene rubber, lithium carboxymethyl cellulose, polyacrylic acid, and polyacrylonitrile; The first ion conductor is at least one of lithium lanthanum titanium oxide, lithium lanthanum zirconium oxide or their doping materials.
4. The solid-state battery according to claim 1, characterized in that: The coating layer comprises at least one of Li3BO3-Li2CO3, Li3PO4, Li4SiO4, Li2ZrO3; and / or, The coating layer has a thickness of 20 nm to 2 μm.
5. The solid-state battery according to claim 1, characterized in that: The negative electrode is prepared by a wet process, and an external magnetic field is applied after the graphite layer slurry is coated to make at least part of the graphite sheets in the graphite layer perpendicular to the negative electrode current collector.
6. The solid-state battery according to any one of claims 1 to 5, characterized in that: The positive electrode comprises a positive electrode current collector and a positive electrode composite layer; The positive electrode composite layer includes a positive electrode active material, and the positive electrode active material particles have a coating layer outside; The positive electrode active material includes at least one of lithium cobalt oxide, lithium nickel cobalt manganese oxide, and lithium-rich manganese-based; The coating layer includes at least one of lithium aluminum titanium phosphate, lithium lanthanum titanium oxide, lithium lanthanum zirconium oxide or their doping materials.
7. The solid-state battery according to claim 6, characterized in that: The coating amount of the coating layer is 0.5wt%~5wt% of the positive electrode active material; and / or, The positive electrode composite layer also includes a conductive agent, a second binder, and a second ion conductive agent; and the mass ratio of the positive electrode active material with a coating layer, the conductive agent, the second binder, and the second ion conductive agent is (70~95):(1~10):(1~5):(1~15).
8. The solid-state battery according to claim 7, characterized in that: The conductive agent includes at least one of conductive graphite, carbon nanotubes, and graphene; The second binder includes at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, vinylidene fluoride-trifluoroethylene, and polytetrafluoroethylene; The second ion-conducting agent includes at least one of a sulfide solid electrolyte and a halide solid electrolyte; wherein the sulfide solid electrolyte is Li 11−x M 2−x P 1+x S 12 (M = Ge, Sn, Si), Li6PS5X (X = Cl, Br, I) at least one; the halide solid electrolyte is Li3MCl6 (M = Y, Er, In, Sc), Li 3−x M 1−x Zr x At least one of Cl6 (M = Y, In, Er, Yb), Li3MBr6 (M = Y, Er, Ho).
9. The solid-state battery according to claim 7, characterized in that: The positive electrode is prepared by a dry method, wherein the positive electrode active material with a coating layer, a conductive agent, a second binder and a second ion conductive agent are mixed and fiberized at 10-25°C, and then pressed into a film at 100-180°C.
10. The solid-state battery according to any one of claims 1-5 and 7-9, characterized in that: The electrolyte includes polytetrafluoroethylene and at least one of a sulfide solid electrolyte, an oxide solid electrolyte, and a halide solid electrolyte; In terms of weight percentage, polytetrafluoroethylene accounts for 1% to 15% of the electrolyte; Sulfide solid electrolyte for Li 11−x M 2−x P 1+x S 12 At least one of (M = Ge, Sn, Si), Li6PS5X (X = Cl, Br, I); The oxide solid electrolyte is at least one of lithium aluminum titanium phosphate, lithium lanthanum titanium oxide, lithium lanthanum zirconium oxide or their doping materials; The halide solid electrolyte is Li3MCl6 (M=Y, Er, In, Sc); The electrolyte is made of polytetrafluoroethylene and at least one of a sulfide solid electrolyte, an oxide solid electrolyte and a halide solid electrolyte, which are mixed and fiberized at 15-30° C. and then pressed into a film at 100-180° C.